Evaluation of the i-STAT analyzer for determination of ionized calcium concentrations in bovine blood - Yilmaz, Oznur; Karapinar, Tolga (Wiley, 2019)
Background Information regarding the performance of the i-STAT, a point-of-care analyzer, to determine ionized calcium (iCa(2+)) concentration in bovine blood is limited. Objective The primary goal of this study was to evaluate the agreement of the i-STAT against a traditional bench-top blood gas analyzer (Radiometer ABL800 FLEX) in the measurement of iCa(2+) in the blood of cattle with various disorders. Methods In this study, 121 cattle with various diseases were used. Venous blood samples were run on the i-STAT and the Radiometer ABL800 FLEX for determination of blood iCa(2+) concentrations. Data were subjected to Passing-Bablok regression and Bland-Altman plots. The Radiometer ABL800 FLEX was the reference method and the i-STAT was the test method. The i-STAT performance was evaluated at two different cutoff values for iCa(2+) concentrations (<1.00 and <1.18 mmol/L) using the receiver operating characteristic curve. Results The Passing-Bablok regression equation that fit the iCa(2+) concentration as measured with the i-STAT (Y) and the Radiometer ABL800 FLEX (X), was Y = -0.108276 [-0.15/-0.06] + 1.103448 [1.06/1.14] x X, with a residual deviation of 0.02. The deviation from the identity line was not significant (P = 0.64). The Bland-Altman difference plot revealed no bias between the i-STAT and the Radiometer ABL 800 FLEX. The i-STAT had a sensitivity of 100% (95% CI, 87.7-100.0) and 94.8% (95% CI, 87.2-98.6) at the iCa(2+) concentration cutoff values of <1.00 and <1.18 mmol/L, respectively. Conclusions iCa(2+) concentrations in bovine blood measured with the i-STAT agreed with those of the Radiometer ABL800 FLEX. In particular, the i-STAT predicted hypocalcemia with a high sensitivity.
Keywords: calcium; cattle; cow; point-of-care; sensitivity